Love, Money, and HIV: Becoming a modern African women in the age of AIDS - Mojola, Sanya A. (California University of California press, 2014)
How do modern women in developing countries experience sexuality and love? Drawing on a rich array of interview, ethnographic, and survey data from her native country of Kenya, Sanyu A. Mojola examines how young African women, who suffer disproportionate rates of HIV infection compared to young African men, navigate their relationships, schooling, employment, and finances in the context of economic inequality and a devastating HIV epidemic.